Clinicopathological features and prognosis of TFE3-positive renal cell carcinoma - Dong, Xiang; Chen, Yuxin; Pan, Jun; Ma, Wenliang; Zhou, Peng; Chen, Ming; Guo, Hongqian; Gan, Weidong (Frontiers in Oncology, 2022)
Background This study aimed to investigate the expression profile of TFE3 in renal cell carcinoma (RCC) and the clinicopathological features as well as prognosis of TFE3-positive RCC. Methods Tissue sections from 796 patients with RCC were collected for immunohistochemical staining of TFE3. Molecular TFE3 rearrangement tests were also carried out on the TFE3-positive RCCs using fluorescence in situ hybridization and RNA-sequencing assays. Both clinicopathological features and follow-up information were collected for further analysis. Results The present study showed that 91 patients with RCC (91/796, 11.4%) were TFE3 positive expression but only 31 (31/91, 34.1%) of the patients were diagnosed with Xp11.2 translocation RCC. Further, it was found that the patients with TFE3-positive RCCs were more likely to develop lymph node and distant metastasis at diagnosis as well as presented a significantly higher WHO/ISUP nuclear grade and AJCC stage as compared with patients with TFE3-negative RCCs (p<0.01). Results of univariate and multivariate analyses showed that TFE3 positive expression was an independent prognostic factor associated with poor progression-free survival. Further, the findings of survival analysis showed that patients with positive TFE3 expression showed a shorter progression-free survival as compared with the patients with negative expression of TFE3 (p<0.001). In addition, results of the survival analysis found that there was no significant difference in progression-free survival between the Xp11.2 translocation RCC and TFE3-positive non-Xp11.2 translocation RCC groups (p=0.9607). Conclusion This study found that nuclear TFE3 expression is not specific to the Xp11.2 translocation RCC. Moreover, the positive TFE3 expression is associated with tumor progression and poor prognosis in patients with RCC irrespective of the presence of TFE3 translocation.